2020
DOI: 10.1111/iwj.13405
|View full text |Cite
|
Sign up to set email alerts
|

Rapid enzymatic burn debridement: A review of the paediatric clinical trial experience

Abstract: NexoBrid (NXB) has been proven to be an effective selective enzymatic debridement agent in adults. This manuscript presents the combined clinical trial experience with NXB in children. Hundred and ten children aged 0.5 to 18 years suffering from deep thermal burns of up to 67% total body surface area were treated with NXB in three clinical trials. Seventy‐seven children were treated with NXB in a phase I/II study, where 92.7% of the areas treated achieved complete eschar removal within 0.9 days from admission.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…The pretreatment risk stratification, adequate monitoring and hemodynamic support are needed when treating patients on more than 15% TBSA [ 15 , 16 , 17 ]. The literature lacks studies reporting the use of enzymatic debridement in children, with the exception of one manuscript presenting the combined experience in the use of Nexobrid ® in pediatric burns throughout three clinical trials, and the study that explores the different possibilities for pain management during enzymatic debridement in pediatric and adult burn patients [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pretreatment risk stratification, adequate monitoring and hemodynamic support are needed when treating patients on more than 15% TBSA [ 15 , 16 , 17 ]. The literature lacks studies reporting the use of enzymatic debridement in children, with the exception of one manuscript presenting the combined experience in the use of Nexobrid ® in pediatric burns throughout three clinical trials, and the study that explores the different possibilities for pain management during enzymatic debridement in pediatric and adult burn patients [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autografting in deep partial thickness wounds was performed in 21.7% of the wounds debrided enzymatically vs. 31.8% of the wounds treated surgically ( p = 0.44). The average long-term modified Vancouver Scar Scale scores were 3.4 for 18 wounds in 8 children treated with Nexobrid ® versus 4.4 for 19 wounds in 9 children debrided using surgical methods [ 18 ]. Another study on adults showed a significant difference in the scar surface appearance (modified Yeong scale), with an average score of 2.5 in the study group, in comparison with 3.2 in SoC patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consenting exceedance of market approval comprised application in paediatric patients [111], utilization for up to 30% TBSA [112], waiver of pre-soaking under certain conditions, applicability for prevention of peripheral BICS, prolonged enzyme application for up to 18 h for improved results, or possible but reluctant retreatment with ED [64,65]. However, explicit surpassing of official recommendations has clearly been pointed out as off-label use.…”
Section: Extended Application Range Based On Expert Consensusmentioning
confidence: 99%
“…Regarding potential side-effects, such as bed bleeding or allergies, they have not been documented in pediatric patients yet, since the clinical trial is still in progress. However, anaphylactic reactions have been noted in patients allergic to pineapple (15) .…”
Section: Escharotomymentioning
confidence: 99%